Effective approaches to financial well-being among university students: a conceptual paper /Amri Mohamad...[et al.] - Mohamad, Amri; Asat, Siti Haliza; Mohamed, Che Rokiah; Abul Hasan Ashari, Anis; Ishak, Rosbi; Wan Ali, Wan Roshaini; Hassan, Othman Zailani (Universiti Teknologi MARA Cawangan Kelantan, 2020)
This is a conceptual paper showing the linkages on the relationship between factors affecting the financial well-being of university students and also the moderating effects of parents’ influence on their financial well-being. The focus on the financial well-being of university students isvery important to ensure that university students do not encounter financial difficulties during their years at universities. To be more specific, this paper examines the four factors which determinethe financial well-being of university students whichare Budget & Financial Education, Structured Funding, Unstructured Funding,and Food Coupon & Book Voucher. The objectives of this research are to establish the extent of the conceptual relationship between four determining factors and the students’ financial well-being. The aims and objectives of this research are accomplished when the conceptualizations of each of the independent variable dimensions and students’ financial well-being are established and the linkages are clearly explained.